Pediatric Obstructive Sleep Apnea Syndrome: Emerging Evidence and Treatment Approach - Maria Rita Giuca; Elisabetta Carli; Lisa Lardani; Marco Pasini; Marco Miceli; Eleonora Fambrini (The Scientific World Journal)
OSA pediatric subjects suffer from episodes of upper airway obstruction that can be partial or complete, with atypical sleep patterns and blood-gas level alteration. If poor treated and/or diagnosed, it can cause cardiovascular disease, learning difficulties, behavioural issues, and retardation of growth. In the literature, there are conflicting evidence about OSA assessment and treatment in pediatric age, so the aim of this paper is to highlight the multidisciplinary approach in the management of sleep disorders, stressing the role of the pediatric dentist in both diagnosing and treating the OSAS in children, according to the current evidence of the treatment options effectiveness of the syndrome itself. Conclusions. Scientific evidence shows that OSAS management requires a multidisciplinary approach in order to make an early diagnosis and a correct treatment plan. The orthodontic treatment approach includes orthopedic maxillary expansion and mandibular advancement using intraoral appliances. Hence, the orthodontist and the pediatric dentist play an important role not only in early diagnosis but also in the treatment of pediatric OSAS.